Managing sewage treatment facilities using geographical information system application: a user requirement analysis in state of Penang, Malaysia - Mohd Zuraini, Idris; Robiah, Suratman; Salfarina, Samsudin; Farah, Zaini (IOP Publishing, 2021)
Rapid development of economy in Malaysia and the large city scale expansion has led to increase in number of domestic sewage and industrial water waste. In managing sewage treatment facilities, Indah Water Konsortium Sdn Bhd (IWK) has developed the Integrated Geographical Information System (IGIS) to help them in decision making process. The face to face interview method with IGIS users has been used in getting the feedback on examining the main attribute data needed and then analyze it by using content analysis. It is conducted by updating the required attribute data into the IGIS application and removing unrelated attributes. In addition, the spatial information that can help to improve the IGIS application also be included in new version. Based on the findings of this paper, the improvement of this information will help the IWK to manage this sewerage system more effectively and to control the increasing number of sewerage treatment plant (STP). The upgraded IGIS application improves the management efficiency, management level and decision-making capacity of sewage treatment in state of Penang and provide a good demonstration and reference in sewage treatment infrastructure in others city.